Influencia de la educación ambiental en la conservación de los bosques aledaños del caserío de Manacamiri - Iquitos- Loreto - 2020 - Alava Arana, Ingrith Wieslawa (2023)
This study was carried out in Manacamiri village, Iquitos district, Maynas province, Loreto region, in order to determine the degree of influence that environmental education offers in the conservation of the forests surrounding Manacamiri village. According to the Likert scale, it was found that the highest scores are categorized as ALWAYS and ALMOST ALWAYS. These results show that there exists a favorably 'HIGH' attitude in topics related to environmental education. The total frequency is 284 responses with 31% of the total and 246 responses with 27% of the total. The responses of ALMOST NEVER AND NEVER, present an unfavorably ‘LOW’ attitude in topics related to environmental education with the scores of 83 responses representing 9% of the total and 161 responses with 17% of the total. Finally, the response SOMETIMES shows a ‘MEDIUM OR NEUTRAL’ attitude on issues related to environmental education of forests, with 150 responses representing 16% of the total. This shows the level of influence of the subjects in relation to environmental education issues. Regarding the felling of trees, the population is aware only in 38% that in their forests this is not frequent and 64% of the population is not aware of the prohibition established by the Ministry of Agriculture. 83% of the population corresponding to the ALWAYS and ALMOST ALWAYS category is willing to support environmental education.